PANDANGAN MAHASISWA TERHADAP PENGGUNAAN ICT DALAM PEMBELAJARAN MATEMATIKA - Nia Monika Sari; Atika Rahayu; Rhomiy Handican (Jurusan Pendidikan Matematika Universitas Borneo Tarakan, 2022)
The role of ICT (Information and Communication Technology) in education is very large in terms of benefits and advantages, namely facilitating broad access to education, being able to improve the quality of learning between students and lecturers. Mastering ICT is a priority that must be understood by everyone including students, but there are obstacles in using ICT such as networks that make it difficult for students to master it. The purpose of this study was to determine how students view the use of ICT in learning Mathematics. This research uses descriptive quantitative with survey method. The data collection instrument used a questionnaire by adapting the online lecture questionnaire for Iain Kerinci students as many as 54 respondents. The findings in this study are that students consider the use of ICT important in the world of education, especially learning mathematics, ICT makes it easier for students to learn mathematics, the use of ICT in learning mathematics, ICT makes it easier for students to find additional references in learning mathematics, the benefits of using ICT in class, a source of student understanding of mathematics material. However, there are obstacles in the use of ICT for students in learning mathematics such as network constraints, quota limitations and unstable networks and the lack of understanding of students themselves about the use of ICT.